Analysis of Character Education Integration On Civics Lesson Plan for Fourth Graders at Primary School - Sari, Apriliani Puspa Arum; Suminar, Tri; Sunarto, Sunarto (Journal of Primary Education)
This research aimed to analyze character education integration into civics lesson plan for fourth graders on theme 9 of How resourceful my country, Indonesia is. The instilled characters into Civics lesson plan were: care, confidence, and responsibility. This qualitative study case technique was conducted at SD N 4 Depok, Toroh district, Grobogan municipal. The techniques of collectin data were interview, observation, and documentation. The validity was done by source and methodology triangulations. The process of analyzing data was done through data reduction, data presentation, and data conclusion/verification. The finding showed that the teacher had been able to instill character education in students. However, the integration of civics lesson plan was not optimum. The lesson plan character was arranged without any modification, especially to develop valuable characters of the students because teacher only transferred what was in her textbook. This lack of integration knowledge of character education in the lesson plan became the main hindrance for teachers. Limited time became the reason of less optimum lesson plan of the teacher. Efforts which could be done is by comprehending the integrative methods of character education in learning and teacher professionalism in managing time wisely so that all tasks could be done.